PERLINDUNGAN HUKUM TERHADAP TINDAK PIDANA PENGANIAYAAN HEWAN PELIHARAAN MENURUT PERSPEKTIF HUKUM PIDANA DI INDONESIA (STUDI PUTUSAN NOMOR: 320/PID.SUS/2020/PT.DKI) - Three Boy (Fakultas Hukum Universitas Tarumanagara, 2021)
Animals are animate creatures that are able to move (move places) and are able to react to stimuli, but do not have reason.Pets are animals whose life is partially or wholly dependent on humans for certain purposes. In this modern era, crimes against pets are rampant. An example is what happened in (Decision Number: 320/Pid.Sus/2020/PT. DKI), where the Defendant Aris Takelabi Padin committed an act of abuse by pouring caustic soda on 5 puppies and 1 mother dog causing 5 puppies. dead dog and 1 deformed mother dog. Animal welfare is all matters related to the physical and mental condition of Animals according to the natural behavior of Animals that need to be implemented and enforced to protect Animals from any person's inappropriate treatment of Animals that are used by humans. From the rampant acts of abuse against these animals, there must be a law that can regulate acts of animal abuse and animal welfare in Indonesia. So that in this study a problem arises in the form of what form of legal protection for pets is in the rules of criminal law in Indonesia and how judges consider in giving decisions on cases (Judgment Number: 320/Pid.Sus/2020/PT. DKI. Implementation of Rules regarding Abuse Animal welfare and animal welfare have been regulated in the Indonesian Criminal Law Regulations, but their implementation is still not optimal. The lightness of the sentence imposed and the lack of socialization, education and public awareness make pet abuse still rampant because this and punishment does not have a deterrent effect Therefore, the Government must pay more attention to and strengthen the punishments contained in the regulations regarding acts of animal abuse and carry out socialization and education to reduce and prevent acts of abuse of pets in Indonesia.